The study of winter barley varieties of different ecological and geographical origins on the main economic-valuable traits and properties - E. G. Filippov; A. A. Dontsova; D. P. Dontsov; I. M. Shapovalova (Зерновое хозяйство России)
The study of winter barley varieties of different ecological and geographical origins on the main economic-valuable traits and properties Barley is a grain crop of multiple uses; its grain can be used for various purposes. Barley productivity greatly varies on different areas of cultivation, that’s why we carry out ecological variety testing to reveal reactions of the varieties on different soil-climatic conditions. It allows selecting cultivars adapted to definite soil-climatic conditions. The purpose of the researches is to study main economic-valuable traits and properties of winter barley varieties in the conditions of the southern part of the Rostov region. The experiments have been conducted in the fields of experimental crop rotation of the department of barley breeding and seed-growing of the FSBSI “ARC “Donskoy” in 2014-2016. The objects of the study were 25 cultivars of winter barley of different ecological and geographical origins. As a result we have selected the varieties with various economic-valuable traits and properties. The varieties “Polet”, “Zhiguli”, “Erema”, “Timofey”, “Artel”, “Samson”, “Platon”, “Gordey”, “Romans”, “Andryusha”, “Espada” (Russia), “Khobbit”, “Vutan”, “Galation” (Switzerland) possess a complex resistance to leaf diseases. The varieties “Erema”, “Timofey”, “Vivat”, “Gordey”, “Romans” (Russia), “Vutan”, “Galation” (Switzerland) are the most productive and resistant to lodging.